2021
DOI: 10.1111/febs.16049
|View full text |Cite
|
Sign up to set email alerts
|

PAM: diverse roles in neuroendocrine cells, cardiomyocytes, and green algae

Abstract: Our understanding of the ways in which peptides are used for communication in the nervous and endocrine systems began with the identification of oxytocin, vasopressin and insulin, each of which is stored in electron dense granules, ready for release in response to an appropriate stimulus. For each of these peptides, entry of its newly synthesized precursor into the endoplasmic reticulum lumen is followed by transport through the secretory pathway, exposing the precursor to a sequence of environments and enzyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 200 publications
0
4
0
Order By: Relevance
“…In the absence of PAM, proANP storage granules failed to form; the reintroduction of PAM facilitated proANP storage. Crucially, enzymatically inactive PAM also supported proANP storage ( 49 , 50 ), leading to the suggestion that PAM acts as a cargo receptor that directly binds to and protects newly synthesized proANP, facilitating its delivery to granules ( 9 , 49 ). A potential role for PAM as a cargo receptor in pituitary cells remains to be explored.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the absence of PAM, proANP storage granules failed to form; the reintroduction of PAM facilitated proANP storage. Crucially, enzymatically inactive PAM also supported proANP storage ( 49 , 50 ), leading to the suggestion that PAM acts as a cargo receptor that directly binds to and protects newly synthesized proANP, facilitating its delivery to granules ( 9 , 49 ). A potential role for PAM as a cargo receptor in pituitary cells remains to be explored.…”
Section: Discussionmentioning
confidence: 99%
“…In a large, international cohort of individuals with PAs, we identified germline loss-of-function (LOF) variants of PAM (peptidylglycine α-amidating monooxygenase, MIM: 170270) in subjects with familial and sporadic GH and ACTH hypersecretion. PAM is a highly conserved, multifunctional protein that is increasingly recognized as an important regulator of peptide amidation and secretion, among many other functions, in health and disease ( 9 ). We functionally evaluated 36 SNVs, demonstrating a deleterious effect on PAM function/expression in eight variants.…”
Section: Introductionmentioning
confidence: 99%
“…Another molecular defect possibly contributing to FIPA was recently proposed, after the finding of germline missense PAM variants in three first-degree relatives with gigantism and in sporadic patients with functioning pituitary tumours [232]. This gene encodes an enzyme catalysing the C-terminal amidation of secreted peptides; LOF was demonstrated in vitro for multiple variants [268,269]. Among these cases, two patients with isolated paediatric CD carried a frameshift and a 5'UTR variant that displayed deleterious effects.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Interestingly, the depletion of proANP in the absence of PAM was unaccompanied by decreased proANP mRNA or protein biosynthesis, but rather occurred due to 3-fold increased basal ANP secretion. Bäck, Mains & Eipper recently suggested that PAM may also have a role as a cargo receptor that directly binds to and protects proANP soon after its synthesis in the rough endoplasmic reticulum through to newly formed granules [9,51]. A potential role for PAM as a cargo receptor in pituitary cells remains to be for use under a CC0 license.…”
Section: 56% (1/18mentioning
confidence: 99%